Feces of Pediculus capitis humanus as sign of viability of the louse. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
When viable lice are not visible on the hair, to find on the hair species specific feces can indirectly confirm their existence. The feces can be barely visible to the naked eye as blackish dots. On the other hand, they can be more easily put in evidence by the dermoscope used with dry technique. The most typical appearance of the louse feces discharged from a short time is that of dark clustered globules, fixed to the hair or free on the surface of the scalp.